ATRT-23. THE DUAL mTORC1/2 INHIBITOR SAPANISERTIB DISRUPTS THE NRF2-MEDIATED STRESS RESPONSE AND COMBINES SYNERGISTICALLY WITH THE BH3 MIMETIC OBATOCLAX TO EXTEND AT/RT SURVIVAL. (4th December 2020) - Parkhurst, Ashlyn; Wang, Sabrina; Alt, Jesse; Arnold, Antje; Kaur, Harpreet; Slusher, Barbara; Eberhart, Charles; Raabe, Eric; Rubens, Jeffrey
Abstract: Atypical teratoid/rhabdoid tumors are aggressive infantile tumors highly resistant to intensive therapies. We aim to identify and target critical factors driving this therapy resistance to improve AT/RT survival. Analysis of publically available RNASeq on 32 AT/RT identified elevated expression of NRF2 (median expression 40.78, normal brain 18.81). NRF2 is a master regulator of cell's stress response whose expression is correlated with therapy resistance and poor survival. NRF2 activation is sensitive to mTOR activity and is a biomarker predicting response to the dual mTORC1/2 inhibitor, Sapanisertib (TAK228, INK128). We performed RNASeq on 4 human-derived AT/RT cell models after Sapanisertib treatment. Pathway analysis reveals disruption of the NRF2-mediated stress response (-log p value 0.39, Z-score 1.0). As a result, Sapanisertib decreases ROS scavengers like glutathione (Metabolite analysis UHPLC-MS, t -test p<0.05) and induces a pro-death phenotype (decreased MCL-1 expression, western blot; gene-expression analysis, RNASeq). The brain-penetrant BH3 mimetic Obatoclax increases ROS generation and induces apoptosis (MUSE oxidative stress and ANNEXIN V assays, t -test p<0.05). These complementary mechanisms of action synergize to induce high rates of cell death (MUSE ANNEXIN V assay, ANOVA p<0.05, C-PARP western blot, Compusyn Synergy analysis CI<1.0) and slow cell growth (MUSE Cell viability, ANOVA p<0.05). Once-weekly treatments of Sapanisertib combined with Obatoclax in orthotopic mouse models of AT/RT are well tolerated, slow tumor growth (bioluminescence imaging) and significantly extend median survival from 35 to 55 days (Log-rank p<0.05). These findings support a new clinical trial aimed at improving AT/RT survival.